2018
DOI: 10.1021/acssuschemeng.8b04340
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposited Nickel Cobalt Sulfide Flowerlike Architectures on Disposable Cellulose Filter Paper for Enzyme-Free Glucose Sensor Applications

Abstract: Three-dimensional flowerlike nickel cobalt sulfide (NiCo 2 S 4 ) nanostructures are electrochemically deposited over the Ni-modified cellulose filter paper (CFP). The fabricated NiCo 2 S 4 /Ni/CFP is explored as a binder-free and self-standing electrode for enzyme-free electrochemical detection of glucose in alkaline media, in which Ni/CFP and NiCo 2 S 4 serve as the current collector and active material, respectively. Owing to the rich redox active sites, synergistic effect between Co 4+ and Ni 3+ , and rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(50 citation statements)
references
References 34 publications
1
49
0
Order By: Relevance
“…The detection limit was estimated 2.98 µM (S/N = 3) (S was the standard deviation of the blank signals for n = 10, and N was the slope of the calibration curve). The sensor behaviors of Zn-Co-S BHS/CNTs were better or comparable to the present reported non-enzymatic glucose sensing based on ternary transition metal oxide/sulfide based materials (Table 1) [37][38][39][40][41][42].…”
Section: Sensors 2020 20 X 4 Of 11supporting
confidence: 81%
See 1 more Smart Citation
“…The detection limit was estimated 2.98 µM (S/N = 3) (S was the standard deviation of the blank signals for n = 10, and N was the slope of the calibration curve). The sensor behaviors of Zn-Co-S BHS/CNTs were better or comparable to the present reported non-enzymatic glucose sensing based on ternary transition metal oxide/sulfide based materials (Table 1) [37][38][39][40][41][42].…”
Section: Sensors 2020 20 X 4 Of 11supporting
confidence: 81%
“…However, no redox peaks was observed at CNTs ( Figure 4 a). This result indicated that redox peaks in the Zn-Co-S BHS and Zn-Co-S BHS/CNTs should be attributed to the existence of Faradaic redox couple species in Zn-Co-S BHS, which might act as active sites to deliver enhanced electrochemical activity during glucose electro-oxidation [ 37 ]. By comparing the CV curves of Zn-Co-S BHN/CNTs with CNTs and Zn-Co-S BHS in 0.1 M NaOH, Zn-Co-S BHS/CNTs exhibited satisfactory electrochemical catalytic activity, which was proposed to derive from the unique conductive network of CNTs providing an ideal conductive contact between Zn-Co-S BHS and CNTs.…”
Section: Resultsmentioning
confidence: 99%
“…Transition metals are low cost and can be used as electrocatalytic materials for glucose. There are many electrocatalysts reported for transition metals, including pure metals [6,25], bimetals [7,26,27,28], compounds [29,30,31,32], and composites [33,34,35,36,37,38,39,40,41,42,43,44] for non-enzymatic glucose sensors. The catalytic principle of non-enzymatic glucose sensors based on transition metals is by using the d-electron of d-orbital to form medium-strength bonds with substrates, so that the analyte can be easily adsorbed at any time, and its products can be easily desorbed [3].…”
Section: Introductionmentioning
confidence: 99%
“…Literature [ 7 , 23 , 25 , 34 , 37 , 47 , 48 , 49 , 50 , 51 , 52 ] has reported that different morphologies of metallic sulfide nanomaterials such as nanowires, nanoplates, hollow ellipsoid, nanotubes, hollow spheres, nanorods, flowerlike structures, core-shell nanoparticles, nanoribbons and complex hierarchal micro/nanostructures been synthesized. Different synthetic approaches, such as dip-coating, chemical vapor deposition (CVD), aqueous one-step wet chemistry, hydrothermal, coprecipitation, exfoliation, sputtering, solid-state reaction, ball-milling and biosynthetic methods, were used to synthesize metal sulfide nanomaterials (shown in Table 1 ).…”
Section: Metallic Sulfide Nanomaterialsmentioning
confidence: 99%